2014
DOI: 10.2967/jnumed.113.135574
|View full text |Cite
|
Sign up to set email alerts
|

A PET Tracer for Brain α2C Adrenoceptors, 11C-ORM-13070: Radiosynthesis and Preclinical Evaluation in Rats and Knockout Mice

Abstract: We report the development of a PET tracer for α 2C adrenoceptor imaging and its preliminary preclinical evaluation. α 2C adrenoceptors in the human brain may be involved in various neuropsychiatric disorders, such as depression, schizophrenia, and neurodegenerative diseases. PET tracers are needed for imaging of this receptor system in vivo. Methods: High-specific-activity 11 C-ORM-13070 (1--(3-11 C-methoxymethylpyridin-2-yl)-piperazine) was synthesized by 11 C-methylation of O-desmethyl-ORM-13070 with 11 C-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 18 publications
(33 reference statements)
4
32
0
Order By: Relevance
“…Tracer metabolism was taken into account in the PET data analysis as the primary analysis was performed with the ratio method which eliminates possible bias caused by radioactive tracer metabolites—as long as there are no treatment‐related alterations in tracer disposition and metabolism. According to previously collected evidence, there was not anticipated to be any specific binding by the metabolites (Arponen et al, : supplemental material). As the metabolites have not been fully characterized, it is possible that they could cause accumulation of radioactivity in the reference region, which may be more pronounced than their nondisplaceable uptake in the target region.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Tracer metabolism was taken into account in the PET data analysis as the primary analysis was performed with the ratio method which eliminates possible bias caused by radioactive tracer metabolites—as long as there are no treatment‐related alterations in tracer disposition and metabolism. According to previously collected evidence, there was not anticipated to be any specific binding by the metabolites (Arponen et al, : supplemental material). As the metabolites have not been fully characterized, it is possible that they could cause accumulation of radioactivity in the reference region, which may be more pronounced than their nondisplaceable uptake in the target region.…”
Section: Discussionmentioning
confidence: 95%
“…Preclinical studies have identified the same fragments and experiments in rats also suggested that one of these compounds (M1), but not the other (M2), can gain access into the brain. The molecular structures of M1 and M2 have not been resolved in spite of extensive efforts involving stable isotopes and mass spectroscopy, but they have been inferred to be volatile, very small molecular weight fragments with no affinity for α 2C ‐ARs (Arponen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, Arponen et al reported an α 2C -selective PET tracer, [ 11 C]ORM-13070. This tracer was evaluated in mice devoid of α 2A -adrenoceptors and mice lacking both α 2A -and α 2Cadrenoceptors in order to confirm its high subtype selectivity [23] and has since been introduced for human use [24].…”
Section: Introductionmentioning
confidence: 99%